Influencia de los controles internos en la mitigación de riesgos: Un enfoque en la conformidad de la información contable - da Silva Brum, Maria Cecília (2023)
This study analyses the influence of internal controls on risk reduction and compliance of accounting information. Qualitative research combined with a quantitative analysis of contents was used applied to a case study. Data were collected through interviews with managers and employees of a public transport institution. The relevance of the study lies in the need to mitigate risks that affect the compliance of accounting information within organizations, given the need for quick and secure information for decision making. The results show in a practical way the compliance of the information through internal controls established at the level of the operational processes of the organization, even if some controls are developed in an informal way. In addition, the results identify technology as the most relevant risk to the organization and legislation as one of the risks inherent to compliance. In addition, the need to integrate strategic and operational risk management to improve information compliance has been identified. The case studied can be transferred to other contexts where it can become a contributory reference for the improvement of internal controls and compliance of accounting information.